Post appendectomy young male proffer intussusception unveiled diffuse large B-cell lymphoma non-Hodgkin lymphoma - Anandakannan, Indrajit; Swaminathan, Shanthi Ponnandai; Kawarat, Vikas; Mani, Rajeshwari; ., Kannan (International Surgery Journal, 2020)
Intussusception is the telescoping of the proximal segment of the intestine within the lumen of the adjacent segment. Adult intussusception is rare and its aetiology differs from paediatrics. Surgery is highly recommended and challenging considering the possibility of carcinoma. Post-operative intussusception is a rare and bizarre complication. We report an 18-year old male who had undergone uncomplicated appendectomy outside the institute with missed histopathological examination (HPE) report, presented with abdominal pain for 1 week, vomiting 4 days, obstipation 1 day. On examination ovoid mass of size (12×7 cm) in right hypochondrium. A plain abdomen radiograph shows dilated bowel loops. Contrast-enhanced computed tomography (CECT) abdomen and pelvis showed telescoping of small bowel into the caecum. Suggestive of post-appendectomy intussusception causing intestinal obstruction, emergency laparotomy revealed telescoping of ileum into caecum, acting as the leading point of intussusception, proceeded with right hemicolectomy and ileo-transverse anastomosis. With blindsiding HPE defining high grade diffuse large B cell lymphoma, immunohistochemistry stains nuclear positivity for cluster of differentiation-20 (CD-20) >80%, and Ki-67 >90%. Surgery plus chemotherapy is warranted being a high-grade tumour. Surgery must be restricted to the primary tumour, with mesenteric lymph node involvement based on oncological principles. Laparoscopic approach is preferred nowadays.